Changing trade trends confronting the Caribbean. - BERNAL, Richard (1996)
Explains the current US/Caribbean Basin framework. Examines the following fundamental and conflicting trade trends confronting the Caribbean, viz; (1) an erosion of historic market access with the US because of preferential trading regime that has been granted Mexico under NAFTA; (2) the NAFTA has signalled a new area of hemispheric cooperation, which will hopefully culminate in the creation of a Free Trade Area of the Americas by the year 2005; (3) the US and the Caribbean Basin countries - along with countries in Central and South America - are embroiled in a dispute over access to the European banana market; and (4) Congress is now working on a proposal to repeal the Section 936 tax credit program, which has acted as one of the largest sources of low cost funds for Caribbean economic development.